Influence of Body Weight and Body Mass Index (BMI) on Serum Creatinine and Creatinine Clearance in Apparently Healthy Adults - O., Festus, O.; G., Ovie, E.; B., Osadolor, H.; C., Ihongbe, J.; V., Osagie, E.; H., Unuabonah, F.; P., Eidangbe A. (Asian Journal of Biological and Life Sciences, 2013)
Serum creatinine and creatinine clearance are widely used clinically as an index of renal function to diagnose, treat and follow up renal diseases. One of the factors influencing the creatinine and its clearance is said to be body weight. To evaluate the influence of body weights on serum creatinine and creatinine clearance, a total of 160 healthy adult subjects (68 males and 92 females), within 1845 years of age were included in this study. The subjects were categorized according to body mass index (BMI): <18.5 kg/m2 (underweight), 18.5-24.9 kg/m2 (normal), 25-29.9 kg/m2 (overweight) and >30 kg/m2 (obese) consisting of 40 subjects respectively. Serum and 2hr urine samples were obtained from all subjects and analyzed using the alkaline picrate method. Astatistical significant difference (P<0.05) was observed for both serum creatinine and creatinine clearance among the various weight categories,due to low values seen in underweight subjects and high values seen in obese subjects. Serum creatinine among males of the various weight categories were found to be significantly different (P<0.05), while their creatinine clearance were not significantly different (P>0.05). Also, serum creatinine and creatinine clearance among females of various weight were found to be significantly different (P<0.05). Also, values observed for males were higher than those of females. This study thus shows that body weight and BMI have significant influence on serum creatinine and creatinine clearance.